Financial Viability and Bankability of JFM Projects in India - Haque, M. S.; Kannapiran, S.; Paul, A. M. (Indian Forester, 1998)
The paper describes the possibilities offundingJFM projects by commercial hanks. The authors opine that to develop India's vast stretch of degraded forest lands of JFM approach is here to stay. Since neither the Centre nor the States have enough financial resources for their rejuvenation there is a strong possibility of the involvement of commercial Banks to finance such projects in near future. Although all JFM projects may not bc bankable, case studies suggest that JFM projects where Teak, Sal and Bamboo are predominant species, there is a strong likelihood of such projects being bankable. It is also presumed that for sustenance of JFM on long term basis continuity of credit will playa major role in future management and protection of our forests.